Efektivitas Program Pembinaan Al-Qur'an dalam Meningkatkan Kemampuan Membaca Al-Qur'an di Kelurahan Borong Kecamatan Tanralili Kabupaten Maros - Akhmad Hanafi Dain Yunta; Rustam Koly (WAHATUL MUJTAMA': Jurnal Pengabdian Masyarakat, 2024)
The Community Service Program (KKN) of STIBA Makassar in Borong Village, Tanralili District, Maros Regency is driven by the phenomenon of the community’s limited knowledge in reading and understanding the Qur’an. Therefore, this study aims to examine the extent of students’ roles in serving the community as a manifestation of the Tri Dharma of Higher Education, particulary in the implementation of Qur’an literacy programs. The method of implementing the community service program begins with mapping the problems and needs of the community using SOAR Analysis. After the analysis is conducted, work programs are formulated according to the community’s needs. Based on the results of the analysis, several programs were designed, including Qur’an Teaching (for children and youth), Arabic Language Teaching, Tahsīn al-Qirā’ah, Ramadan Intensive Courses, Funeral Management Training, Distribution of Iqra’ Books, Righteous Children Festival, Grand Tabligh, Distribution of Preachers and Tarawih Imams, Ramadan Qur’an Recitation and Iftar Distribution, and Social Service Activities. All these programs have been successfully implemented and have shown initial results in line with the objectives set for the KKN.